"How do I paint it?" (Indianapolis, IN Design Video Communications, 1988)
Shows a variety of scene painting techniques and explains, step by step, how to execute them.
DVD
Introduction--.
Supplies & tools--.
Cross hatching--.
Spattering--.
Feather dusting--.
Keywords: Theaters -- Stage-setting and scenery; Painting -- Technique